2005
DOI: 10.4049/jimmunol.175.11.7151
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-Phosphate Agonists Increase Macrophage Homing, Lymphocyte Contacts, and Endothelial Junctional Complex Formation in Murine Lymph Nodes

Abstract: The sphingosine-1-phosphate (S1P) receptor agonist, phosphorylated FTY720 (FTY-P), causes lymphopenia, lymphocyte sequestration in mesenteric lymph nodes (MLNs), and immunosuppression. Using multiple techniques to analyze MLN cells harvested from mice treated with S1P receptor agonists, we saw a redistribution of lymphocytes out of nodal sinuses and an expansion of follicles. Although changes in circulating monocytes were not observed with overnight exposure to FTY720, we saw a significant increase in S1P rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 56 publications
(63 reference statements)
9
78
1
1
Order By: Relevance
“…However, an effect on circulating monocytes has not been reported. Moreover, FTY720 has been shown to increase the number of macrophages in mesenteric lymph nodes, suggesting that S1P receptors may be important for monocyte egress from lymph nodes in a manner similar to lymphocytes (20). However, it is not clear whether this is a direct or indirect effect on either the numbers or trafficking of circulating monocytes.…”
mentioning
confidence: 77%
“…However, an effect on circulating monocytes has not been reported. Moreover, FTY720 has been shown to increase the number of macrophages in mesenteric lymph nodes, suggesting that S1P receptors may be important for monocyte egress from lymph nodes in a manner similar to lymphocytes (20). However, it is not clear whether this is a direct or indirect effect on either the numbers or trafficking of circulating monocytes.…”
mentioning
confidence: 77%
“…In fact, interactions between S1P, SK and various catenin family members have been described. [79][80][81][82][83] A recent study demonstrated that Sphk1, the major enzyme necessary for synthesizing S1P, is required for enlargement of Min mouse adenomas, since Min mice that do not express this enzyme develop only small adenomas, in contrast to the significant number of large adenomas that developed in Min mice with intact Sphk1 expression. 84 Importantly, both S1P and sphingosine levels were high in Min mouse polyps compared to normal adjacent tissues, indicating that sphingolipid metabolism is abnormal in the neoplastic tissue.…”
Section: S1p Lyase Sownregulation In Intestinal Tumorigenesismentioning
confidence: 99%
“…Further, in a recent multiple sclerosis clinical trial, FTY720 increased rates of dyspnea and decreased lung function (lowered forced expiratory volume in 1 second) (88), perhaps mediated through mechanisms similar to those seen in the S1P-induced contraction of bronchial smooth muscle in mice (67). Importantly, FTY720-P induced the ubiquitination and proteasomal degradation of S1P 1 in cultured ECs (84) and HEK293 cells (89). Prolonged exposure to FTY720 resulted in the down-regulation of the EC surface expression of S1P 1 and decreased responses to S1P (90).…”
Section: Limitations Of Fty720 and Fty720-p As Therapeutic Agents In Alimentioning
confidence: 99%
“…However, although FTY720 increased the expression of protein phosphatase 2A, it did not alter FTY720-induced barrier enhancement (83). FTY720 also up-regulated the expression of EC junctional proteins b-catenin and zonula occludens protein 1 (ZO-1) (71), and it promoted adherens junction assembly (84). However, ECs treated with specific siRNAs against claudin-5 or ZO-1/ZO-2 did not alter FTY720-induced barrier enhancement, suggesting that adherens junction or tight junction proteins are not involved in FTY720-induced barrier enhancement (83).…”
Section: Mechanisms Of Barrier Regulation By Fty720 and Fty720-pmentioning
confidence: 99%